Public opinion communication mechanism of public health emergencies in Weibo: take the COVID-19 epidemic as an example - Ren, Siguo; Gong, Chao; Zhang, Chen; Li, Chen (Frontiers in Public Health, 2023)
As a major public health emergency, the COVID-19 epidemic not only has a real risk of infection, but also easily generates public opinion risks. Under the condition of social communication of microblog, how to effectively identify public opinion and the harm of public health emergencies, avoid the overlay of real risk of epidemic and network public opinion risk, and prevent and resolve major public opinion risks is an important public opinion research topic in the new era. Taking the most influential outbreak of COVID-19 pneumonia in China in 2020 as an example, this paper discusses the effect of sudden major public health cases on Chinese microblogs and the spreading mechanism of public opinion. This paper mainly explores the communication motivation of public opinion from the four communication elements of the microblog public opinion center, public opinion object, public opinion carrier and public opinion ontology. And combined with the life cycle theory, this study analyzes the interaction between the communication elements of public opinion in different stages. In the fluctuation period of public opinion, the amount of public opinion information decreases relatively, and the frequent occurrence of secondary public opinion in the outbreak period promotes the continuation of public opinion. Compared with the diversified demands of public materials and medical assistance during the pandemic, public opinion in the fluctuation period reacts on the epidemic situation, which to some extent alleviates the tension of the epidemic situation. Based on this, this study puts forward the guidance strategy of public opinion of public health emergencies.